2014
DOI: 10.1007/s13244-014-0377-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease—the role of cross-sectional imaging techniques in the investigation of the small bowel

Abstract: Background: The diagnosis of inflammatory bowel disease (IBD) in children and adolescents is based on the integration of clinical, biological, endoscopic, histological and radiological data. Methods: The most important part of the diagnosis is the histology, which is acquired by endoscopy. Imaging of the small bowel has changed in recent years, but the imaging goals are primarily to determine the extent of small bowel involvement, assess complications and define candidates for surgery. Imaging techniques are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…However, MRI is expensive and is not easily accessible for all IBD patients. US is a noninvasive, radiation‐free, and inexpensive modality compared with CT, MRI, and endoscopy . Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MRI is expensive and is not easily accessible for all IBD patients. US is a noninvasive, radiation‐free, and inexpensive modality compared with CT, MRI, and endoscopy . Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity .…”
Section: Discussionmentioning
confidence: 99%
“…US is a noninvasive, radiation-free, and inexpensive modality compared with CT, MRI, and endoscopy. 24,25 Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity. 13,26 A recent meta-analysis showed that US has a high diagnostic accuracy for detecting CD.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor disease activity and to guide appropriate treatment, CD patients require multiple imaging examinations repeatedly [ 8 ]. Cross-sectional techniques have advanced the ability to diagnose, classify, and monitor CD [ 9 ]; the desirable imaging modality would be one that is reproducible, free of ionizing radiation, and well tolerated. MR-E is a noninvasive technique not relying on ionizing radiation, showing high values of sensitivity and specificity in CD assessment [ 10 ] and nowadays the standard protocol is based on morphologic unenhanced images and on dynamic fast 3D spoiled gradient echo T1 fat-suppressed postcontrast sequence that evaluates the pattern of bowel wall enhancement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These agents are used for the delineation of extra‐enteric structures, fistulae, abscesses, lymphadenopathy, wall thickening, luminal narrowing, and other abnormalities. CTE is by far the most widely used of the modalities for evaluation of IBD and numerous references may be found in the literature with respect to the use of CTE for IBD . CTE has, however, lower spatial resolution when compared to conventional enterography, as motion artifacts (caused by peristaltic motion) may greatly reduce image quality.…”
Section: Current Clinical Diagnostic Imaging Of Ibdmentioning
confidence: 99%